English pronunciation teaching at different educational levels: Insights into teachers’ perceptions and actions - Szyszka, Magdalena (Research in Language, 2016)
The aim of the present paper is to reflect upon the place of pronunciation in English as a foreign language (EFL) teaching at different educational levels in Poland. To collect the data, an on-line survey was conducted among EFL professionals teaching at primary, lower secondary, and higher secondary schools in Poland. The questions focused on the respondents’ beliefs about pronunciation, teachers’ competences regarding pronunciation and pronunciation teaching, and the pronunciation teaching techniques they use. The results depict the most and least frequently used pronunciation teaching techniques at each of the three educational stages, and the beliefs of EFL teachers in Poland regarding pronunciation teaching.